Preoperative Butyrylcholinesterase Level as an Independent Predictor of Overall Survival in Clear Cell Renal Cell Carcinoma Patients Treated with Nephrectomy - Takuya Koie; Chikara Ohyama; Jotaro Mikami; Hiromichi Iwamura; Naoki Fujita; Tendo Sato; Yuta Kojima; Ken Fukushi; Hayato Yamamoto; Atsushi Imai; Shingo Hatakeyama; Takahiro Yoneyama; et al. (The Scientific World Journal)
The prognostic factors for the overall survival (OS) of clear cell renal cell carcinoma (ccRCC) patients treated with nephrectomy are not well defined. In the present study, we investigated the prognostic significance of preoperative butyrylcholinesterase (BChE) levels in 400 ccRCC patients undergoing radical or partial nephrectomy from 1992 to 2013 at our institution. Univariate and multivariate analyses were performed to determine the clinical factors associated with OS. Among the enrolled patients, 302 were diagnosed with organ-confined disease only (T1-2N0M0), 16 with lymph node metastases, and 56 with distant metastases. The median preoperative BChE level was 250 U/L (normal range, 168–470 U/L), and median follow-up period was 36 months. The 3-year OS rate in patients with preoperative BChE levels of ≥100 U/L was significantly higher than in those with levels of <100 U/L (89.3% versus 77.7%, P=0.004). On univariate analysis, performance status; anemia; hypoalbuminemia; preoperative levels of BChE, corrected calcium, and C-reactive protein; and distant metastasis status were significantly associated with OS. Multivariate analysis revealed that preoperative BChE levels and distant metastasis status were significantly associated with OS. Our findings suggest a possible role of preoperative BChE levels as an independent predictor of OS after nephrectomy in ccRCC patients.